Simultaneous production of antioxidants and starch from the microalga Chlorella sorokiniana - Petruk, Ganna; Roxo, Mariana; Wink, Michael (Algal Research, 2018)
In recent years, microalgae have gained considerable importance as potential source of biofuels and bioplastics. However, these markets are still developing, as the high costs of cultivation ask for exploiting microalgae into new areas and with a biorefinery approach towards a multicomponent cascade extraction process. Here, a sequential processing strategy was used to extract starch with high yield from Chlorella sorokiniana under biocompatible conditions. The extract residue was then tested as a potential source of antioxidants. We found a strong protective activity of the extract residue towards oxidative stress in vitro on human colon cancer cells and in vivo on Caenorhabditis elegans nematodes, by inhibiting ROS production and activating DAF-16/FOXO transcription factor pathway. A pool of molecules from three different classes (fatty acids, photosynthetic pigments and carotenoids) was identified as responsible for the antioxidant activity. To our knowledge, this is the first report on the obtainment, from a “waste” fraction, of high value products endowed with antioxidant activity tested in cell-based models and in vivo.